2012
DOI: 10.1016/j.cub.2012.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Why Middle-Aged Listeners Have Trouble Hearing in Everyday Settings

Abstract: Summary Anecdotally, middle-aged listeners report difficulty conversing in social settings, even when they have normal audiometric thresholds [1–3]. Moreover, young adult listeners with “normal” hearing vary in their ability to selectively attend to speech amid similar streams of speech. Ignoring age, these individual differences correlate with physiological differences in temporal coding precision present in the auditory brainstem, suggesting that the fidelity of encoding of suprathreshold sound helps explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
108
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(125 citation statements)
references
References 44 publications
15
108
2
Order By: Relevance
“…Features of the FFR vary between people, even within a neurologically normal young adult population (Hoormann et al, 1992;Ruggles et al, 2012;Coffey et al, 2016a). These differences have been linked to musical (Musacchia et al, 2007;Bidelman, 2013) and language (Wong et al, 2007) experience and have been shown to be cognitively and behaviorally relevant, for example, in the perception of speech in noise (Ruggles et al, 2012), consonance and dissonance (Bones et al, 2014), and in pitch perception bias (Coffey et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Features of the FFR vary between people, even within a neurologically normal young adult population (Hoormann et al, 1992;Ruggles et al, 2012;Coffey et al, 2016a). These differences have been linked to musical (Musacchia et al, 2007;Bidelman, 2013) and language (Wong et al, 2007) experience and have been shown to be cognitively and behaviorally relevant, for example, in the perception of speech in noise (Ruggles et al, 2012), consonance and dissonance (Bones et al, 2014), and in pitch perception bias (Coffey et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…These differences have been linked to musical (Musacchia et al, 2007;Bidelman, 2013) and language (Wong et al, 2007) experience and have been shown to be cognitively and behaviorally relevant, for example, in the perception of speech in noise (Ruggles et al, 2012), consonance and dissonance (Bones et al, 2014), and in pitch perception bias (Coffey et al, 2016a). Similarly, the MEG FFR-f 0 signal attributed to the right auditory cortex in our prior study was correlated with musical experience and fine frequency (FF) discrimination ability (Coffey et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence has shown that the loss of hearing thresholds due to changes in the periphery does not account for all the changes in hearing seen with age (Dubno et al 1984;Ruggles et al 2012;Fullgrabe et al 2015). Neural deficits due to loss of spiral ganglion and ribbon synapses (Sergeyenko et al 2013) or imbalances in the composition of neurotransmitters (Caspary et al 2008) in the central auditory pathway could account for the deficits seen in temporal processing and sound segregation at suprathreshold sound levels, which persist in subjects with clinically Bnormalĥ earing thresholds (Hind et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Neural deficits due to loss of spiral ganglion and ribbon synapses (Sergeyenko et al 2013) or imbalances in the composition of neurotransmitters (Caspary et al 2008) in the central auditory pathway could account for the deficits seen in temporal processing and sound segregation at suprathreshold sound levels, which persist in subjects with clinically Bnormalĥ earing thresholds (Hind et al 2011). These neural deficits can be detected objectively in both human populations and animal models using auditory evoked potentials such as auditory brainstem responses (ABRs) a n d e n v e l o p e f o l l o w i n g r e s p o n s e s ( E F R s ) (Parthasarathy and Bartlett 2011;Ruggles et al 2012;Sergeyenko et al 2013;Shaheen et al 2015). EFRs represent summed, sustained, synchronized activities of populations of neurons from the auditory pathway which provide additional complementary information to metrics obtained from more established responses like ABRs (Parthasarathy et al 2014), with the major generators being the auditory brainstem and midbrain (Kuwada et al 2002;Chandrasekaran and Kraus 2010;Parthasarathy and Bartlett 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ruggles et al (2012) showed that these interindividual differences correlated with physiological differences in temporal coding precision in the auditory brainstem. Since brainstem encoding of sound has been related to several factors involving experience (e.g., musical training and reading proficiency; for a recent review, see Hornickel and Kraus, 2012), it remains an open question whether individual experience could be more relevant to differences in auditory selective attention than sex and age, as were investigated here.…”
Section: Sex Differences Across the Life Spanmentioning
confidence: 99%